2016
DOI: 10.1080/00927872.2016.1236933
|View full text |Cite
|
Sign up to set email alerts
|

A note on a paper by Cuadra, Etingof and Walton

Abstract: Abstract. We analyse the proof of the main result of a paper by Cuadra, Etingof and Walton, which says that any action of a semisimple Hopf algebra H on the nth Weyl algebra A = An(K) over a field K of characteristic 0 factors through a group algebra. We verify that their methods can be used to show that any action of a semisimple Hopf algebra H on an iterated Ore extension of derivation typeThe purpose of this note is to analyse the main result of the paper [3] which says that any action of a semisimple Hopf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In [14], by using and analyzing the results obtained by Cuadra, Etingof and Walton, it was showed that any semisimple Hopf action over an algebraically closed field of characteristic zero on an skew polynomial ring of derivation type must factor through a group action. Although there are examples in literature of Hopf actions on quantum polynomial algebras that do not factor through group actions (see [13, 7.4-7.6]), in this paper we give some conditions to define an action of a Hopf algebra on an skew polynomial of automorphism type which does not factor through a group action (Theorem 3.1).…”
Section: Introductionmentioning
confidence: 99%
“…In [14], by using and analyzing the results obtained by Cuadra, Etingof and Walton, it was showed that any semisimple Hopf action over an algebraically closed field of characteristic zero on an skew polynomial ring of derivation type must factor through a group action. Although there are examples in literature of Hopf actions on quantum polynomial algebras that do not factor through group actions (see [13, 7.4-7.6]), in this paper we give some conditions to define an action of a Hopf algebra on an skew polynomial of automorphism type which does not factor through a group action (Theorem 3.1).…”
Section: Introductionmentioning
confidence: 99%